Intercultural Studies of Curriculum Theory, Policy and Practice (Intercultural Studies in Education, 2018)
This book explores the philosophical, ideological and practical dimensions of curriculum using an intercultural lens. It is cross-cultural, comparative and inclusive, with each chapter featuring case studies from a minimum of three countries across different continents. By using the same methods of data collection and analysis for each country level in each chapter, the text explores relationships of curriculum theory, policy and practice both within and between countries. A diverse range of themes is explored, including; social justice and teacher preparation curriculum, language education curriculum, early childhood education and music, curriculum as praxis, curriculum and globalisation, science curriculum, teacher leadership in curriculum implementation, as well as curriculum and history. The exploration of these themes lays the foundation for open dialogue and innovative approaches in exploring curriculum issues within, between and across cultures and contexts.